Design and Build a Coconut Ripeness Classifier Using Sound Sensor - Yoyok Heru; Rachmad Saptono; Agin Syahansyah (Politeknik Negeri Malang, 2022)
The difference in the texture of coconut flesh is an obstacle for sellers of coconut drinks who use young coconut meat with a soft texture, and an obstacle for industries that use old coconut meat with a hard texture, such as the production of coconut milk, coconut oil and coconut flour. Therefore, consistency in determining the thickness of the coconut flesh is very much needed.This research will design a tool to classification and classify the maturity of sound sensor coconut fruit. In determining young or old coconuts based on sound,a servo motor as a driving force to use the outside of the coconut to make sound.This test is done by testing the original type of green coconut. Based on the results of testing the coconut fruit maturity classification tool using a sound sensor, it can be done and the sound sensor successfully captures sound. Coconut fruit can be classified as young if it has a sound intensity of less than 56 dB, because the coconut fruit has the characteristics of a young coconut, which is small in size, bright green in color and has pink fibers. Meanwhile, if the resulting sound intensity is more than 56 dB, the coconut is classified as an old coconut because the coconut has the characteristics of an old coconut, which is brown or dark green in color, large in size and has white fibers. Speed and power Servo Motor has to be the same input voltage of 5Volt.